Level of financial literacy of academic youth from rural areas in the Visegrad Group countries - Szafrańska, Monika (Poziom świadomości finansowej młodzieży akademickiej z obszarów wiejskich w krajach Grupy Wyszehradzkiej, 2019)
The aim of the study is to determine the level of financial literacy of academic youth from rural areas in the V4 Group countries, as well as to compare the results obtained with the level of financial literacy of young people from cities. The source of data used for analysis and inference were primary information obtained from own research (PAPI method, 900 people). The research used a set of questions to assess the level of financial literacy of adults proposed by the OECD INFE. In addition to primary sources, secondary sources were also used to achieve the goal. The measures of descriptive statistics and one-way analysis of variance (F) were used. The level of financial literacy was determined at the medium level, which may indicate the low effectiveness of financial education measures implemented at different levels of education. The component of financial literacy where students from rural areas had the lowest scores was basic financial knowledge. Only 43% of people from rural areas achieved the minimum target score
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 3, s. 46-58
Keywords: financial awareness; university students; village; V4 Group; Visegrad Group; świadomość finansowa; studenci; obszary wiejskie; kraje Grupy Wyszehradzkiej